On the polysemy of Spanish spatial Ps - Ursini, Francesco; Giannella, Adriano (Borealis – An International Journal of Hispanic Linguistics, 2016)
The goal of this paper is to investigate the polysemy of Spanish spatial prepositions (a, en, hacia, among others), and offer a syntactic and semantic treatment of this phenomenon. The core idea behind this account is that these prepositions can denote sets of possible locations that are involved in spatial relations. Consequently, the compositional interaction of polysemous prepositions with other parts of speech can determine which specific sense emerges in a sentence. The analysis is couched in a Type-Logical Grammar approach. It addresses data that have not previously been analysed in the literature, involving so-called Boolean constructions (e.g. en la estación y la calle). Also, the paper shows that a single treatment can capture all the relevant data. Therefore, the analysis shows that polysemy is a grammar phenomenon that is better accounted for in architectures with a distinct syntactic/derivational component (e.g. Distributed Morphology), than in architectures lacking this component (e.g. Cognitive Linguistics approaches). Consequences for a theory of grammar are discussed.